Fenomena Umroh Mandiri Terhadap Bisnis Perjalanan Wisata Di Indonesia - Dirgantara, Ahmad Rimba; Syaiba Amalia Syamsiah; Laila Ramadhina; Pangestika, Irawan (Universitas Persatuan Islam, 2025)
This study examines the phenomenon of independent Umrah and its impact on the travel business in Indonesia, focusing on two significant provinces: South Sumatra and West Java. This research aims to analyze the factors driving the popularity of independent Umrah and its implications for the dynamics of the travel industry. Primary data was collected through in-depth interviews with three informants: independent Umrah participants, government representatives from the Hajj and Umrah sector at the Ministry of Religious Affairs, and travel business operators. Data analysis utilized a qualitative thematic approach to identify patterns and relationships among variables. The findings indicate a significant increase in public interest in independent Umrah, primarily due to its more affordable cost than conventional packages and flexibility in arranging schedules and itineraries. However, this phenomenon has disrupted traditional Umrah travel businesses, which face declining demand and must adapt their marketing strategies. Conversely, general travel business operators have started integrating support services for independent Umrah, such as local transportation rentals and specialist guides, as new business opportunities. The study also highlights regulatory challenges, including potential misuse of travel permits and the need for stricter oversight by relevant authorities. The implications of this research emphasize the need for collaboration among the government, business operators, and communities to create a sustainable, equitable, and Sharia-compliant Umrah travel ecosystem. This study recommends digital-based business model innovations to enhance the competitiveness of conventional travel operators.